Development of Flashcard Media Based on Augmented Reality (AR) on Solar System Material for Grade VI Elementary School - Fitriyani, Nurul; Rintayati, Peduk; Salimi, Moh (Universitas Sebelas Maret, 2025)
In this digital era, technological developments are rapidly advancing and undoubtedly influencing various aspects of life. One such area is education. Driven by these rapid technological advancements, the education sector is required to adapt to technological progress in order to create a more effective and interactive learning process that engages students and meets the needs of the times. This study aims to conduct a literature review analysis on the use of augmented reality (AR) media. The method used in this study is a Systematic Literature Review of 20 articles, namely 10 national articles and 10 international articles from 2020 to 2025. The articles were selected according to the criteria to be analysed. The results show that augmented reality (AR)-based learning media has consistently proven to be feasible, practical, and effective in various subjects. Augmented reality (AR) can increase motivation, conceptual understanding, critical thinking skills, numeracy literacy, interest in reading, and even student learning outcomes. Validation from subject matter experts, media experts, and users generally shows a rating of good to very feasible, with positive responses from both teachers and students. Thus, AR can be an innovative solution to make learning more interactive, interesting, and meaningful at various levels of education.